Merit Pay, Scientific Production, and the Comisión Nacional Evaluadora de la Acitividad Investigadora del Profesorado Universitario - Gema Polo; Gustavo R. De las Heras (The Evaluation Center at Western Michigan University, 2008)
Some authors have given the CNEAI (National Commission for the Evaluation of Research Activity) a notorious role in the promotion of scientific research in Spain when considering the requirements for this institution as one of the essential elements in the increase of the Spanish scientific production in the last few years. We hereby expose that the increase of the scientific production in Spain is not linked either with the evaluation activity of the research fulfilment done by the CNEAI, nor consequently with the merit pay system done specifically in Spain by means of an economic incentive called "sexenios." On the contrary, we suggest that such increase is related to the growth of both human and material resources devoted to the research activity, a conclusion that may sound obvious at first sight, but it's necessary to point out for those who (some times in a selfish way) deny it. Moreover, it is shown how the so-called merit pay system presents notorious risks that must be addressed to avoid unwanted effects. All in all, we do consider that a system of economic incentives based on a correct evaluation of the research activity can be effective in improving the quality of scientific production, as well as gradually improve everyone's way of working.